2014
DOI: 10.1130/g35432.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for fluvial bedrock incision by suspended and bedload sediment

Abstract: Fluvial bedrock incision sets the pace of landscape evolution and can be dominated by abrasion from impacting particles. Existing bedrock incision models diverge on the ability of sediment to erode within the suspension regime, leading to competing predictions of lowland river erosion rates, knickpoint formation and evolution, and the transient response of orogens to external forcing. We present controlled abrasion mill experiments designed to test fl uvial incision models in the bedload and suspension regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
108
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 25 publications
4
108
0
Order By: Relevance
“…4a-b) for kv = 9 x 10 5 and β = 2. This value of kv is similar to the range of values calculated for bedrock erosion (kv ~ 10 6 , Dietrich, 2004 andLamb et al, 2008; kv ~ 3 x 10 5 , Scheingross et al, 2014). As in the total-load bedrock erosion model (Lamb et al, 2008;Scheingross et al, 2014), the ooid precipitation-abrasion model accounts for viscous damping of particle-bed impacts using a threshold particle Stokes number, St =…”
Section: Text S2 Single Particle Abrasion Modelsupporting
confidence: 52%
See 3 more Smart Citations
“…4a-b) for kv = 9 x 10 5 and β = 2. This value of kv is similar to the range of values calculated for bedrock erosion (kv ~ 10 6 , Dietrich, 2004 andLamb et al, 2008; kv ~ 3 x 10 5 , Scheingross et al, 2014). As in the total-load bedrock erosion model (Lamb et al, 2008;Scheingross et al, 2014), the ooid precipitation-abrasion model accounts for viscous damping of particle-bed impacts using a threshold particle Stokes number, St =…”
Section: Text S2 Single Particle Abrasion Modelsupporting
confidence: 52%
“…S10) is Stc = 9, lower than that identified for total-load bedrock erosion (Stc = 75; Scheingross et al, 2014) , but consistent with the critical Stokes number, Stc ~ 5-10, identified as the threshold below which particle deformation during a collision is negligible (Davis et al, 1986;Joseph et al, 2001). The lower Stokes limit might also be due to the roughened bed in the ooid experiments, as compared to a smooth bedrock bed in the experiments of Scheingross et al (2014).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…During the rapid phase of gorge formation, abrasion was considered to be minimal as the river sediment load would have been largely entrapped within the reservoir behind the dam. Although negligible, some erosion by abrasion may have occurred within the plunge pool associated with dislodgement and transport of the scoured blocks from the plunge pool 13,43,44 . None of the existing documentation or photographs observed within the archives suggests any evidence to support spring seepage as an active process at any stage of erosion.…”
Section: Discussionmentioning
confidence: 99%